Experimental studies of dark current in a superconducting rf photoinjector - R. Xiang; A. Arnold; T. Kamps; P. Lu; P. Michel; P. Murcek; H. Vennekate; G. Staats; J. Teichert (Physical Review Special Topics. Accelerators and Beams, 2014)
A superconducting rf photoinjector (SRF gun) has been put in operation successfully at the radiation source ELBE. It produces a 13 MHz, low emittance, cw beam with beam current up to 400  μA and energy of 3 MeV. During the gun operation, the field emission from the niobium cavity and the Cs_{2}Te cathodes produces dark current. In this paper, we study the dark current of the SRF gun by using the existing diagnostics beam line. The dependency of the intensity and the energy spectrum on the cavity gradient and the cathode voltage are examined, and the emission sources are analyzed. Furthermore, the new project of installing a strip line kicker to reduce the dark current effect is presented.